Perceptions of Hanoi University of Science and Technology Students about Blended Learning - Duyen, Nguyen Thi; Huong, Bui Thi Thu; Doc, Nguyen Van; Thuy, Le Thi Thu (VNU Journal of Science: Education Research, 2025)
The paper aims to understand students' awareness of blended teaching in the following aspects: The necessity of blended teaching; The effects of combined teaching on learners; Necessary level of activities to implement combined teaching for students. Data was collected through a survey on google form with 127 students studying at Hanoi University of Science and Technology. Research results have shown: Students appreciate the necessity of combined teaching because this activity brings certain benefits to learners. To effectively implement combined teaching, it is necessary to deploy many different activities from "Designing PowerPoint lessons"; “Compiling electronic learning materials” to “Establishing online learning groups”.